2005
DOI: 10.1007/s00018-004-4349-8
|View full text |Cite
|
Sign up to set email alerts
|

?-1,3-Fucosyltransferase-VII stimulates the growth of hepatocarcinoma cells via the cyclin-dependent kinase inhibitor p27Kip1

Abstract: After the transfection of alpha-1,3-fucosyltransferase (FucT)-VII cDNA into H7721 human hepatocarcinoma cells, the protein expression of some cyclins, cyclin-dependent kinases (CDKs) and cyclin-dependent kinase inhibitors (CDIs) p16INK4 and p21waf1/Cip1 were unchanged. However, CDI p27Kip1 protein, both the total amount and the amount that bound to CDK2, but not its mRNA, was significantly reduced. The de-inhibited CDK2 stimulated the phosphorylation of retinoblastoma (Rb) protein and facilitated the G1/S tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…We further explored the biological changes of LOVO cells after stable transfection of FucT-VII in vitro. Previous studies showed that the tranfection of FucT-VII into H7721 hepatocarcinoma cells could enhance phosphorylation of retinoblastoma (Rb) protein and facilitate the G1/S transition and growth rate of the cells through the regulation of CDI Kipl protein (31). In our study, we transfected ·1,3 FucT-VII into human colon cancer cells and yielded a similar result.…”
Section: Discussionsupporting
confidence: 71%
“…We further explored the biological changes of LOVO cells after stable transfection of FucT-VII in vitro. Previous studies showed that the tranfection of FucT-VII into H7721 hepatocarcinoma cells could enhance phosphorylation of retinoblastoma (Rb) protein and facilitate the G1/S transition and growth rate of the cells through the regulation of CDI Kipl protein (31). In our study, we transfected ·1,3 FucT-VII into human colon cancer cells and yielded a similar result.…”
Section: Discussionsupporting
confidence: 71%
“…In addition to the MAPKs, another protein kinase Akt is able to mediate cell growth via the phosphorylation of a variety of substrates (Cicenas, 2008;de Souza et al, 2009). Many studies have implicated the regulating MAPK and PI3K/Akt signaling as likely mechanisms for regulation of cell cycle in human cancer cells by glycosyltransferases (Wang et al, 2005;Wang et al, 2007). However, limited information is available on the significance of MAPK and PI3K/Akt pathway as potential targets for FUT4.…”
Section: Discussionmentioning
confidence: 98%
“…28,29 Accordingly and having shown that FUT1 selectively and quantitatively inhibits sLe x synthesis in HepG2 cells, we investigated the capacity of FUT1-expressing cells to develop tumors. To this end, cells were subcutaneously inoculated to nu/nu nude mice and results from two independent experiments, using 12 animals per each experiment, are shown in Figure 2.…”
Section: Fut1 Strongly Inhibits Tumor Formation In Nude Micementioning
confidence: 99%